Syncopal reactions in blood donors: Pathophysiology, clinical course, and features - Abhishekh Basavarajegowda; Y. C. Nalini (Asian Journal of Transfusion Science)
Vasovagal syncope (VVS) in donors is a transient loss of consciousness due to short-term global cerebral hypoperfusion, which has a rapid onset and has complete spontaneous recovery. VVS may be triggered by pain, fear, anxiety, or emotional upset and loss of blood perse. It is an exaggeration of an adaptive response meant to assist in reducing the amount of bleeding/loss of blood. The four major components necessary for rapid cardiovascular adjustments to supine or upright posture, otherwise called orthostasis, are the autonomic nervous system, adequate blood volume, and intact skeletal and respiratory muscle pumps. The taxing of these autoregulatory mechanisms and their inability to compensate sufficiently results in VVS. VVR episodes can be described in 3 phases; Presyncope, Syncope, and Postsyncope. The actual syncope generally lasts for <15 s, comprising staring, muscle jerks, eye deviation/rolling, sometimes incontinence, loss of consciousness, gasping, snoring, apnea, inability to move/react, etc., The postsyncopal phase is the longest, which is generally manifested as fatigue.